Environment and Culture: Adaptations that have Shaped Nepal - Rai, Anu (Unity Journal, 2023)
Nepal has a wide variety of environmental conditions owing to its unique geographical position, wide ranging altitude (59 m to 8848.86 m), and diverse climatic conditions. To adapt to such environmental conditions, different cultural practices have been adopted; specific cultures enabled harmonization with the environment. In this study, I have discussed how different cultural practices came into being because of diverse environmental conditions in Nepal. I have shed light on select cultural practices of different ethnic groups enabling adaptation to the environment. Conversely, I have also provided instances of how cultural practices have shaped the environment settings. To undertake this study, I have employed literature review on ecological anthropology of Nepal. Key Informant Interviews and observations have further complemented the study. The study helps to understand the prominent role of environmental conditions in shaping cultural practice in Nepal. This informs the cultural resilience that Nepalese society have exhibited over time and provides an appreciation of environmental cultural relations.